PENERAPAN MEDIA PEMBELAJARAN KOMIK DIGITAL UNTUK MENGATASI KESULITAN BELAJAR SISWA KELAS 2B MINU KEDUNGREJO PADA MATA PELAJARAN PKN MATERI ATURAN DIRUMAH DAN DI SEKOLAH - Ananda Chumairoh; Aulia Mufidatus Safiani; Putri Yasmin Fazia Risfi; Nur ‘Aisyatir Rodliyah; Muchammad Bachrul Alam; Asnal Mala (Universitas Muhammadiyah Tapanuli Selatan, 2026)
In today's digital era, teachers are expected to be more competent in delivering learning materials to create an interactive and enjoyable learning environment. Therefore, the use of learning media is crucial, not merely as a supplement, but as an effective tool to help students understand the material more easily. Media plays a significant role in the learning process. However, the teacher's role is also crucial in ensuring that the media used is not boring and can motivate students to learn. This research focuses on the development of learning media in the form of digital comics presented in video format, specifically covering the rules and benefits. Furthermore, this study aims to determine students' responses to the created digital comics. The research used research and development (RD) methods. The media development process followed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. This study involved one teacher and 21 students who actively participated in the learning process. In addition, one material expert and one media expert participated in this study. Data were collected through observations, questionnaires, interviews, and tests. The results showed that the video-based digital comic media was rated